Achievement of Strategic Plan Targets and Their Implications for Program Performance: an Evaluative Study of The Regional Office of The Ministry of Religious Affairs In Bengkulu Province - Muhamad Pratama (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2026)
This study aims to analyze the relationship between the achievement of Strategic Plan (Renstra) targets and program performance at the Regional Office of the Ministry of Religious Affairs of Bengkulu Province in 2024. The background of this study is rooted in the importance of evaluating the effectiveness of the implementation of the 2020–2024 Strategic Plan in improving results-based public institutional performance. This study employs a quantitative descriptive approach using secondary data obtained from the Performance Reporting and Accountability Information System (SIPKA) of the Ministry of Religious Affairs. The analyzed data consist of the 2024 Performance Report, covering 48 activity targets and 118 performance indicators. Data were collected through documentation study, while data analysis was conducted using descriptive statistics and simple linear regression with the assistance of IBM SPSS version 26. The results indicate that the average performance achievement reached 119.9%, with a performance quality index of 99.69%, demonstrating that the implementation of programs at the Bengkulu Regional Office of the Ministry of Religious Affairs exceeded the established strategic targets. Regression analysis reveals a positive and significant effect of Strategic Plan target achievement on program performance, with a correlation coefficient (r) of 0.93 and a coefficient of determination (R²) of 0.86. This implies that 86% of the variation in program performance is explained by the level of Strategic Plan target achievement. The study concludes that the achievement of the Strategic Plan significantly contributes to the improvement of program performance and underscores the importance of data-based reporting systems such as SIPKA in strengthening public accountability and transparency. Practically, these findings provide a foundation for strengthening data-driven strategic planning policies in the formulation of the Ministry of Religious Affairs’ Strategic Plan for the subsequent period.